Expression and enzymatic characterization of rice α-galactosidase II displayed on yeast cell surface. (June 2019) - Dong, Mosi; Li, Tuoping; Li, Suhong; Guo, Jia; Gong, Yun; Qi, Xin
Graphical abstract: Highlights: Yeast surface display (YSD) rice α- Gal II was constructed. Ascorbic acid significantly increased YSD rice α-Gal II expression efficiency and activity. YSD rice α-Gal II exhibited higher thermal, pH, and storage stability and hydrolytic activity. Abstract: A yeast ( Saccharomyces cerevisiae EBY100) surface displayed rice α-galactosidase II (YSD rice α-Gal II) was constructed. The optimum temperature and pH of YSD rice α-Gal II were 45 °C and 4.0–5.5, respectively. Ascorbic acid significantly increased the expression level of YSD rice α-Gal II by 5.7-fold, compared to control, indicating its importance in the production and application of YSD rice α-Gal II. Meanwhile, protective agents including Fe 3+, EDTA, urea, andl -arginine also enhanced YSD rice α-Gal II activity by a certain extent (15–78%). Furthermore, YSD rice α-Gal II exhibited higher thermal, pH, and storage stability, and remarkable hydrolytic activity toward defatted soybean meal and guar gum. Hence, YSD rice α-Gal II has great potential for degradation of the non-digestible and flatulence-causing oligo- or poly-saccharides and could be a commendable candidate for extensive application in food and feed industries.